Accumulation of Heavy Metals in the Agricultural Soils Close to the Industrial Drains/Areas - Adnan Iqbal, Muhammad; Nawaz Chaudhry, Muhammad; Zaib, Shujah; Vaqas, Muhammad; Imran, Muhammad (Asian Journal of Chemistry, 2010)
The present study is conducted to assess the accumulation of heavy metals in some selected urban and peri-urban agricultural areas in Faisalabad. The purpose of study is to investigate the extent of soil contamination in those areas which are either irrigated or not-irrigated by the industrial waste water but are either close to industrial sectors or industrial waste water drainages. All the soil samples were analyzed for different heavy metals including Cd, Cr, Cu, Ni, Hg, Pb, Mn and Zn by atomic absorption spectrophotometer. Mercury was determined by using cold vapour technique. All the soil samples were found within permissible ranges with respect to Pb, Mn and Zn. The level of mercury was found much higher than the permissible level in some samples. The higher levels of Ni and Pb were found in the soil samples collected from the surroundings of ghee mills.